Figure of merit for the thermal performance of cementitious composites containing phase change materials. (January 2016) - Thiele, Alexander M.; Wei, Zhenhua; Falzone, Gabriel; Young, Benjamin A.; Neithalath, Narayanan; Sant, Gaurav; Pilon, Laurent
Abstract: This paper presents a novel method to quantitatively characterize the thermal performance of composite materials containing phase change materials (PCM) based on a figure of merit we termed the energy indicator. The method features (i) commonly used specimen geometry, (ii) straightforward experimental implementation, and (iii) sensitivity to relevant design parameters including PCM volume fraction, enthalpy of phase change, composite effective thermal conductivity, and specimen dimensions. The experimental method and the concept of energy indicator were demonstrated on PCM-mortar composites using various volume fractions of two commercial microencapsulated PCMs. This was supported by transient two-dimensional heat transfer simulations. The energy indicator was shown to increase linearly with increasing microencapsulated PCM volume fraction and latent heat of fusion and quadratically with the specimen radius. This figure of merit can be used to rapidly screen and select microencapsulated PCM composite materials for energy efficient buildings or crack-resistant concretes.